Some Thoughts on Qallunaat Teacher Caring in Nunavut - Paul Berger (University of Windsor, 2007)
Qallunaat (non-Inuit) teaching Inuit students in Nunavut risk being agents of the continuing colonialism of EuroCanadian schooling. I argue that for a Qallunaat teacher to be a caring teacher this, and related issues, must be faced. I claim that an extraordinary commitment, expressed in actions, is required from individual teachers, and discuss the near impossibility of truly caring in the absence of change in the very Western way schooling is conducted in Nunavut.